Motivation and mental well-being of long-distance hikers: A quantitative and qualitative approach. Issue 5 (May 2021) - Mayer, Krisztina; Lukács, Andrea
Abstract: Hikers performing long distances (1000–5500 kms a year) were analyzed using quantitative and qualitative methods to evaluate their mental well-being and to find their motivation as well as to analyze the excessive physical activity. 112 hikers completed a questionnaire (M(age) = 40.28, SD = 8.77, 57.1% male) and 25 individuals were interviewed. Distance had association only with perceived health status. There were no differences between males and females, as well as between age groups and educational attainments regarding distance. 33.3% of hikers indicated symptoms of loneliness and 4.5% were involved excessively in hiking that was significantly regressed by distress. Hikers had mainly intrinsic motivations to complete long distances including overcoming new challenges, finding the physical boundaries, experiencing a state outside the comfort zone, belonging to a special group with similar interest and attracted by the beauty of nature. Overcoming all these embodied in a flow experience that took them further to perform the new long-distance trails. Abstract : Excessive physical activity, Flow experience, Hikers, Long distance, Loneliness, Mental well-being